STRATEGI PENJUALAN MAKANAN MELALUI MEDIA DIGITAL: GOFOOD, GRABFOOD DAN SHOPEEFOOD - Fajriyah Salsabila Halim; Rafika Rahmawati; Siti Mardiah (DEVOSI, 2022)
The purpose of this community service is to help overcome the problem for MSME actors to use digital applications in developing their business as well as a means to promote through digital marketing. Various digital marketing strategies through digital applications, including Gofood, Grabfood and Shopeefood. The methodology used is descriptive qualitative with interviews, observations and socialization to MSME actors. Data is collected through documents and literature related to digital marketing and digital applications that are widely used today. This study found that digital marketing strategies have a role in promoting products. The entire digital marketing strategy, both in planning, implementing, and evaluating, has its own uniqueness. This shows that the sales strategy through digital media has been going well and provides more benefits to MSME actors in helping develop businesses, especially in the food sector by using the Gofood, Grabfood and Shopeefood applications.